2023
DOI: 10.3389/fnhum.2023.1130231
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive rehabilitation in multiple sclerosis: Three digital ingredients to address current and future priorities

Abstract: Multiple sclerosis (MS) is a neurological chronic disease with autoimmune demyelinating lesions and one of the most common disability causes in young adults. People with MS (PwMS) experience cognitive impairments (CIs) and clinical evidence shows their presence during all MS stages even in the absence of other symptoms. Cognitive rehabilitation (CR) aims at reducing CI and improving PwMS’ awareness of cognitive difficulties faced in their daily living. More defined cognitive profiles, easier treatment access a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 58 publications
(63 reference statements)
0
0
0
Order By: Relevance
“…This aligns results from previous studies that highlighted the potentialities of a digital tool for cognitive assessment in MS [23,58,59]. As indicated by Tacchino et al [60], digital cognitive assessments, expected to occur more frequently, at home or in an unsupervised setting, could also support the integration with electronic PROs of other dimensions significant for MS (e.g., mood). Brichetto et al…”
Section: Limitations and Strengthssupporting
confidence: 89%
“…This aligns results from previous studies that highlighted the potentialities of a digital tool for cognitive assessment in MS [23,58,59]. As indicated by Tacchino et al [60], digital cognitive assessments, expected to occur more frequently, at home or in an unsupervised setting, could also support the integration with electronic PROs of other dimensions significant for MS (e.g., mood). Brichetto et al…”
Section: Limitations and Strengthssupporting
confidence: 89%
“…In this context, remote rehabilitation protocols offer a promising alternative to traditional in-person rehabilitation. TR addresses mobility-related issues and has the potential to reduce healthcare costs [7,8]. Furthermore, it is worth noting that prior studies have suggested that the clinical effectiveness of TR may be comparable to or even superior to traditional rehabilitation programs [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…TR addresses mobility-related issues and has the potential to reduce healthcare costs [7,8]. Furthermore, it is worth noting that prior studies have suggested that the clinical effectiveness of TR may be comparable to or even superior to traditional rehabilitation programs [7,8]. Various authors have also demonstrated that the benefits of TR are enhanced when used in conjunction with VR, which provides concrete, sustainable, and realistic experiences [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation